Impact of Total Quality Management on Business Performance at DIY MSMEs Mediated by Customer Satisfaction and Moderated by the JIT - Nurul Faroh Almuna; Wulandari, Novi Diah; Rifqi Syarif Nasrulloh (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
The research investigates how Total Quality Management (TQM) influences company performance, with customer satisfaction acting as a mediator and the Just In Time (JIT) concept functioning as a moderator. This study specifically targets micro, small, and medium enterprises (MSMEs) in the food and craft industries in Yogyakarta. With a quantitative methodology, the study uses purposive and non-probability sampling techniques to collect data from 125 participants in DI Yogyakarta. The Smart-PLS application is used to analyze data using structural equation modeling (SEM) methods.The findings showed that total quality management (TQM) significantly improves positive effect both customer satisfaction and business perfomance. However, there is also a strong positive correlation between customer satisfaction and business performance. Other results show that the JIT variable improves business performance, but has a negative and insignificant impact in moderating the effect of TQM that it can actually weaken MSMEs TQM. MSMEs' commitment to maintaining product quality is the main thing that affects customer satisfaction and improves business performance. Thus, strict supervision is needed in the production process, including quality data collection, supplier selection, employee training, production timeliness, as well as regular inspections.